What is the best way to help someone grow: through encouragement or criticism? (Journal of Parents and Teachers, 2026)
This article analyses the effectiveness of motivation versus upbringing in education, assessing their impact on development and performance. It classifies motivational approaches and suggests practical exercises for parents and educators.
Keywords: Encouragement; criticism; motivation; basic needs; attitudes